ABC of Common Grammatical Errors - Turton N. D. Nigel (Oxford, Macmillan, 1995)
A reference book for learners and teachers of English as a second or foreign language. Its main aim is to provide intermediate and advanced learners with access to the information they need in order to correct their grammatical errors. For teachers, it provides a checklist of learners' errors, together with explanations of the relevant grammatical points. The book covers errors in system grammar and errors in word grammar, as well as "common" errors, namely, those that are made by learners of various language backgrounds. The guide employs standard British English, and the differences between British English and American English usage are described at the relevant entries. The entries feature examples of correct and incorrect usage, followed by an explanation of the rule which has been broken.